Cash Holding, Firm Value and Performance under Financial Constraint: A Case Study of the Iranian Capital Market - Azadeh Shemshad; Mohsen Imeni (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study was conducted to gather evidence to investigate the relationship between cash holdings, firm value, and financial performance of companies' constraints in financing the Iranian capital market.Methodology: This study was investigated for 91 companies (number of observations 728) in 8 years between 2012 and 2019. Also, panel data regression was used to test the relationships between variables.Findings: The results indicate a nonlinear relationship between cash holdings and performance, and this relationship is inverted U-shaped. Also, this relationship has existed with the performance variable (ROE) as an alternative variable. This study shows a negative relationship between the non-optimal level of cash holdings and financial performance. The results indicate that companies with financial constraints hold cash holdings, which will reduce financial performance.Originality/Value: Evidence of a nonlinear relationship between firm performance and cash holdings under company-specific conditions gives managers and investors the insight to examine the performance of companies, future value, and how they make decisions in certain circumstances, such as financial constraints for companies